TI_GERICHTE 12.2013.187 vom 11. November 2015 , Avvocato - responsabilità per pratiche risarcitorie verso una banca - TI Tribunale d'appello (2015)
Avvocato - responsabilità per pratiche risarcitorie verso una banca